2011
DOI: 10.1007/s10900-011-9377-3
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Deprivation, Supermarket Availability, and BMI in Low-Income Women: A Multilevel Analysis

Abstract: High levels of neighborhood deprivation and lack of access to supermarkets have been associated with increased risk of obesity in women. This multilevel study used a statewide dataset (n = 21,166) of low-income women in the Special Supplemental Nutrition Program for Women, Infants, and Children to determine whether the association between neighborhood deprivation and BMI is mediated by the availability of retail food stores, and whether this relationship varied across the urban rural continuum. Residence in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
3
16
0
1
Order By: Relevance
“…Many acculturation measures assess language use and comfort with the use of native language; however, emerging thought considers that other factors, such as length of time in the country and contextual nuances of neighborhood life, might contribute to sedentary behavior and obesity [6668]. Research suggests that immigration status, length of residence in the U.S., socioeconomic status, and residential environment might play a much larger role in the health statue of culturally diverse and immigrant women than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Many acculturation measures assess language use and comfort with the use of native language; however, emerging thought considers that other factors, such as length of time in the country and contextual nuances of neighborhood life, might contribute to sedentary behavior and obesity [6668]. Research suggests that immigration status, length of residence in the U.S., socioeconomic status, and residential environment might play a much larger role in the health statue of culturally diverse and immigrant women than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Richardson et al [86••] found that neighborhood race disparities were most pronounced in lowdensity urban (largely suburban) areas where high-poverty/ high-minority areas had lower availability of grocery/supermarkets, and conveniences stores, and greater availability of fast-food restaurants than low-poverty/low-minority areas. Nevertheless, few studies consider variability in retail food environment effects based on urbanicity [87]. Healthy food availability, affordability, and quality might be a proxy for other aspects of neighborhood deprivation, such as crime and low economic viability, which may also contribute to poor dietary intake and obesity risk [88].…”
Section: Discussionmentioning
confidence: 99%
“…First, youth in lower-SES level communities may experience structural disadvantages including less access to healthy food [16,17], limited safe environments to exercise [18], and environmental health risk factors such as substandard housing and dangerous street traffic [19,20]. These structural disadvantages may damage youth's health and carry over into adulthood [21,22] increasing the risk for CVD.…”
Section: Mechanisms Of Community Health Effectsmentioning
confidence: 99%